Procurement of Deceased Donor Parathyroid Glands With the Aid of Near-infrared Autofluorescence Imaging. Issue 4 (10th March 2022) - Ward, Casey J.; Kelly, Yvonne M.; Syed, Shareef M.; Meier, Raphael P.H.; Ando, Tadasuke; Wisel, Steven A.; Gardner, James M.; Stock, Peter G.; Duh, Quan-Yang
Abstract : Background: Parathyroid allotransplantation is a burgeoning treatment for severe hypoparathyroidism. Deceased donor parathyroid gland (PTG) procurement can be technically challenging due to lack of normal intraoperative landmarks and exposure constraints in the neck of organ donors. In this study, we assessed standard 4-gland exposure in situ and en bloc surgical techniques for PTG procurement and ex vivo near-infrared autofluorescence (NIRAF) imaging for identification of PTGs during organ recovery. Methods: Research tissue consent was obtained from organ donors or donor families for PTG procurement. All donors were normocalcemic, brain-dead, solid organ donors between 18 and 65 y of age. PTGs were procured initially using a standard 4-gland exposure technique in situ and subsequently using a novel en bloc resection technique after systemic organ preservation flushing. Parathyroid tissue was stored at 4 °C in the University of Wisconsin solution up to 48 h post-procurement. Fluoptics Fluobeam NIRAF camera and Image J software were utilized for quantification of NIRAF signal. Results: Thirty-one brain-dead deceased donor PTG procurements were performed by abdominal transplant surgeons. In the initial 8 deceased donors, a mean of 1.75 glands (±1.48 glands SD) per donor were recovered using the 4-gland in situ technique. Implementation of combined en bloc resection with ex vivo NIRAF imaging in 23 consecutive donors yielded a mean of 3.60 glands (±0.4 SD) recovered per donor ( P < 0.0001). Quantification of NIRAF integrated density signal demonstrated >1-fold log difference in PTG (2.13 × 10 5 pixels) versus surrounding anterior neck structures (1.9 × 10 4 pixels; P < 0.0001). PTGs maintain distinct NIRAF signal from the time of recovery (1.88 × 10 5 pixels) up to 48 h post-procurement (1.55 × 10 5 pixels) in organ preservation cold storage ( P = 0.34). Conclusions: The use of an en bloc surgical technique with ex vivo NIRAF imaging significantly enhances the identification and recovery of PTG from deceased donors.